Hospital Chaplaincy in the Twenty-first Century The Crisis of Spiritual Care on the NHS. - Swift, Christopher (Farnham : Ashgate Publishing Ltd, 2014)
This book charts the changing role of hospital chaplains and examines through detailed case studies the realities of practice and the political debates which either threaten or sustain the service. This second edition includes a new introduction and updated material throughout to present fresh insights and research about chaplaincy, including in relation to New Atheism and the developing debate about secularism and religion in public life.
6 Religion, Secularization and SpiritualityIntroduction; Decline in Religious Observance; A Secular Age; Religious Care; Spiritual Care; Conclusion; 7 Theological Voices and Ventures; Introduction; Practical Theology; Who are Health Care Chaplains?; What the Chaplain Comes For: Licensing Sermon 1997; Theological Engagement; Heterotopias as a Conceptualization for the Chaplain's Space; Conclusion; 8 Conclusion; Introduction; Chaplaincy in a Time of Change; Critical Choices; The Hidden Dynamics of Health Care Chaplaincy; Occupying Multiple Marginalities; Spiritual Care in a Material World
Description based upon print version of record.
BibliographyIndex
Keywords: Chaplains, Hospital -- Great Britain; Great Britain. National Health Service -- Chaplains; Great Britain. -- National Health Service -- Chaplains; Chaplains, Hospital -- Great Britain; RELIGION / Christian Life / General; RELIGION / Christian Ministry / Adult; RELIGION / Christian Ministry / Counseling & Recovery; Electronic books